Pemodelan 3D Perubahan Coulomb Stress Pasca-Gempa Seram Pada 5 Mei 2024 Dengan Magnitudo 6.1 Mw - Riski Wahyudi; Laila Auliya; Purwaditya Nugraha; Nugroho Prasetyo; Yudha Styawan (Universitas Negeri Gorontalo, 2025)
This study aims to analyze Coulomb stress changes following the Mw 6.1 earthquake in Seram on May 5, 2024, in order to identify potential subsequent seismic hazards. The methodology employed numerical modeling using Coulomb 3.4 to calculate stress distribution, which was then visualized through spatial interpolation in both 2D maps and 3D cross-sections. The 2D modeling results reveal zones of significant stress increase that spatially correlate with the locations of major earthquakes in 1993 and 1998. The 3D analysis further indicates stress concentration at shallow to intermediate depths (0–12 km), consistent with the distribution of recorded aftershocks, thereby validating the reliability of the model. Additionally, stress transfer was detected toward surrounding faults, particularly the Seram strike-slip segment and the Bobot fault segment. In conclusion, this research demonstrates that Coulomb stress modeling provides a quantitative framework for assessing post-seismic stress evolution and constitutes a crucial basis for disaster mitigation efforts in the tectonically complex Maluku region.